Cashmere cyclic growth affected by different photoperiods alters DNA methylation patterns - Ruoyang Zhao; Tiecheng Wu; Jun Yin; Tao Wang; Yunmei He; Yahan Wu; Yulin Gao; Bin Liu (All Life)
Whole-genome bisulfite sequencing was used to study epigenetic differences in hair follicles from Inner Mongolia Albas cashmere goats during long and short photoperiods. Results showed earlier anagen entry in short photoperiod. Genome-wide cytosine methylation was 3.23%, with CG, CHG, and CHH methylation rates at 48.00%, 0.19%, and 0.17%, respectively. Methylation was higher for CG than for CHG and CHH, and higher for introns than exons and downstream regions. Both groups had similar levels of CG, CHG, and CHH methylation, but CHH methylation levels differed slightly between photoperiods. A total of 9,700 differentially methylated regions (DMRs) and 4,187 genes (DMGs) were identified. Gene Ontology (GO) and KEGG analyses revealed significant enrichment in 67 GO terms and 41 signaling pathways related to circadian rhythms, bringing new insights in the role of DNA methylation in cashmere growth and development.